Assessing the Effectiveness of Traffic Education Programs on Driving Practices in Ghana - Sakyi-Yeboah, Emmanuel; Fosu, Gabriel Obed; Aninwaa, Matilda; Lawer, Emmanuel Kofi (The Indonesian Institute of Science and Technology Research, 2025)
Traffic education is crucial in enhancing driver skills, improving road safety, and reducing traffic-related accidents. This study investigates the impact of traffic education on driver behavior, focusing on differences between private and commercial drivers and the influence of driving experience across key content areas, including Traffic Laws and Regulations, Basic Driving Skills, Hazard Awareness, and Road Courtesy. The study employed descriptive and inferential statistical analyses to assess participation rates and the effectiveness of traffic education programs. The results show that Basic Driving Skills emerged as the most frequently engaged and effective content area, while Road Courtesy and Impaired Driving training received little attention. Significant disparities were observed in participation, with private drivers engaging more consistently in structured educational programs than their commercial counterparts. The analysis also indicates that drivers with fewer years of experience report higher impacts from traffic education, underscoring the importance of early and continuous engagement in training programs. Notably, the study found no significant difference in the effects of traffic education based on years of driving experience, highlighting the need for a comprehensive revision of traffic education programs to address these gaps and improve road safety outcomes.